Plenary council closing mass-homily - Costelloe, Timothy M. (The Australasian Catholic record, 2023)
Last Sunday evening, when the members of the Plenary Council came together to enter into the extraordinary and very challenging week which is now coming to an end, we found ourselves gathering around the tomb of Saint Mary of the Cross MacKillop, our first and, so far, only, homegrown Australian saint. We began with the now traditional and very important acknowledgement of country. The spirituality of the first inhabitants of this land has taught us a great deal about the importance and the sacredness of place, and as the smoke from the smoking ceremony spread through the chapel it was as if we were moving into something new and something special. And, of course, we were. The place where Mary MacKillop is buried is indeed a sacred space for us as Christians, and especially for us as Catholics.